Allogeneic stem cell transplantation in AML with t(6;9)(p23;q34);DEK‐NUP214 shows a favourable outcome when performed in first complete remission. (5th February 2020) - Díaz‐Beyá, Marina; Labopin, Myriam; Maertens, Johan; Alijurf, Mahmoud; Passweg, Jakob; Dietrich, Beelen; Schouten, Harry; Socié, Gerard; Schaap, Nicolaas; Schwerdtfeger, Rainer; Volin, Liisa; Michallet, Mauricette; et al.
Summary: Acute myeloid leukaemia (AML) with t(6;9)(p23;q34) is a poor‐risk entity, commonly associated with FLT3‐ ITD (internal tandem duplication). Allogeneic stem‐cell tranplantation (allo‐SCT) is recommended, although studies analysing the outcome of allo‐SCT in this setting are lacking. We selected 195 patients with t(6;9) AML, who received a first allo‐SCT between 2000 and 2016 from the EBMT (European Society for Blood and Marrow Transplantation) registry. Disease status at time of allo‐SCT was the strongest independent prognostic factor, with a two‐year leukaemia‐free survival and relapse incidence of 57% and 19% in patients in CR1 (first complete remission), 34% and 33% in CR2 (second complete remission), and 24% and 49% in patients not in remission, respectively ( P  < 0·001). This study, which represents the largest one available in t(6;9) AML, supports the recommendation to submit these patients to allo‐SCT in CR1.